Autoimmune gastritis in autoimmune thyroid disease. Issue 7 (3rd February 2015) - Venerito, M.; Radünz, M.; Reschke, K.; Reinhold, D.; Frauenschläger, K.; Jechorek, D.; Di Mario, F.; Malfertheiner, P.
Summary: Background: Autoimmune gastritis leads to oxyntic gastric atrophy, a condition at increased risk for gastric cancer. Autoimmune gastritis in conjunction with autoimmune thyroid disease has been reported previously. Aim: In a case–control study in patients with autoimmune thyroid disease to evaluate the usefulness of serum pepsinogens for the identification of oxyntic gastric atrophy, and to determine the relationship of Helicobacter pylori with oxyntic gastric atrophy. Methods: Patients with autoimmune thyroid disease (cases) and goitre (controls) were prospectively enrolled in the study. Pepsinogen (PG) I levels ≤25 μg/mL and PG I/II ratio ≤3 were indicative for oxyntic gastric atrophy. Antibodies against H. pylori, CagA and parietal cells were also determined. Esophagogastroduodenoscopy with biopsies was offered to patients with serological oxyntic gastric atrophy. Results: In total, 34 autoimmune thyroid disease patients and 30 controls were enrolled. Serological oxyntic gastric atrophy was present only in autoimmune thyroid disease patients (8/34, 23.5%, OR 8.3, 95% CI = 1.9–36.2). In all eight patients oxyntic gastric atrophy was confirmed by histology. OLGA stage I, II, III and IV was described in 0%, 33%, 50% and 17% of the cases, respectively. About, 89% and 11% of oxyntic gastric atrophy patients were seropositive for antibodies against parietal cells or H. pylori infection, respectively. Gastric atrophy involved the angulus/antrum in 50% of patients with autoimmune gastritis. Conclusions: The seroprevalence of oxyntic gastric atrophy is high in patients with autoimmune thyroid disease, and testing of serum pepsinogens should be included in the clinical assessment of these patients. H. pylori infection is unlikely to be a principal factor in the pathogenesis of oxyntic gastric atrophy in patients with autoimmune thyroid disease. In autoimmune gastritis, gastric atrophy can spread from the oxyntic towards the antral mucosa.